2021
DOI: 10.1016/j.cmi.2020.11.011
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and geographical area of origin

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…The influence of Latin American origins in the prognosis of SARS-CoV-2 infections is controversial [ 13 ]. The CDC registers report that Latin Americans could be disproportionately represented among deaths attributed to COVID-19 [ 6 ] or have a more severe form of the illness [ 9 ], corroborating data from other studies in which COVID-19 fatalities in this sub-population could be around 1.5–2 times higher [ 1 , 4 , 7 ] than among Caucasians, although this finding is not consistent across all studies [ 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The influence of Latin American origins in the prognosis of SARS-CoV-2 infections is controversial [ 13 ]. The CDC registers report that Latin Americans could be disproportionately represented among deaths attributed to COVID-19 [ 6 ] or have a more severe form of the illness [ 9 ], corroborating data from other studies in which COVID-19 fatalities in this sub-population could be around 1.5–2 times higher [ 1 , 4 , 7 ] than among Caucasians, although this finding is not consistent across all studies [ 14 , 15 , 16 ].…”
Section: Discussionsupporting
confidence: 55%
“…In Spain, which features a homogeneous national public healthcare system, Norman et al [ 9 ] conducted a retrospective analysis of 2345 hospitalized patients with confirmed COVID-19 infections, and, after adjusting by race/gender, showed that there were no significant differences in mortality between Europeans and non-Europeans (mainly Latin Americans (91%))(OR 1.27, 95% CI: 0.86–1.88). However, an increase in ICU admission rates was found in non-Europeans (OR 1.43, 95% CI: 1.03–1.98).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ndings of two previous studies of Spanish and immigrant COVID-19 patients hospitalised in Spain (including a majority of immigrants from Latin America) are different: one did not nd any signi cant difference in mortality between patients of European and non-European origin [12], and the other found that mortality was actually lower among the immigrants [11]. The foreign-born patients in these studies had similar demographic characteristics to those of our immigrant patients, but the lack of additional information concerning the clinical drivers of COVID-19 outcomes (such disease severity or the prevalence of obesity) makes it di cult to make a more detailed comparison.…”
Section: Discussionmentioning
confidence: 68%
“…It has also been observed that immigrants are at greater risk of exposure and infection than native populations, probably because they often work in high-risk occupations, live in overcrowded accommodation, and face barriers to healthcare and prevention initiatives [9,10]. Some studies have found that immigrants with COVID-19 are also at increased risk of hospitalisation [9,10], but it is unclear whether this means that they are also at increased risk of COVID-19-related death [11,12].…”
Section: Introductionmentioning
confidence: 99%